2016
DOI: 10.1002/jsfa.8146
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide induces disease resistance against Monilinia fructicola through activating the phenylpropanoid pathway in peach fruit

Abstract: These results suggest that NO treatment could activate the phenylpropanoid pathway to enhance the activity of related enzymes and the contents of phenylpropanoid metabolites in peach to improve disease resistance and prevent pathogenic invasion. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 56 publications
(55 reference statements)
7
51
0
Order By: Relevance
“…; Li et al . ) as well as prevent browning in apple (Pristijono et al . ), or delay softening in mango and strawberry (Zaharah & Sing ; Zhu & Zhou ), all of which are usually caused by oxidation during fruit storage and transportation.…”
Section: Nitric Oxide (No) a Novel Regulator Of Fruit Ripeningmentioning
confidence: 99%
“…; Li et al . ) as well as prevent browning in apple (Pristijono et al . ), or delay softening in mango and strawberry (Zaharah & Sing ; Zhu & Zhou ), all of which are usually caused by oxidation during fruit storage and transportation.…”
Section: Nitric Oxide (No) a Novel Regulator Of Fruit Ripeningmentioning
confidence: 99%
“…In response to fungal infection during postharvest life, phenylpropanoid pathway activity is fundamental for enhancing decay resistance in fruits and vegetables, resulting from a direct inhibition of spore germination and mycelium growth by phenols or elimination of fungal pathogens by phenols by quinine production, and a deposition of phenols in the cell wall, which serves as a physical barrier to fungal infection, restricting fungal sparring . Kim and Hwang also reported that the higher PAL gene expression and activity were responsible for attenuating pathogen infection in pepper as a result of signaling H 2 O 2 accumulation, generated by higher NADPH oxidase gene expression, resulting in higher endogenous SA accumulation and higher PR1 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…also reported that the promotion of PAL enzyme activity and higher endogenous SA accumulation, resulting in higher PRs gene expression, accompanied by higher ROS scavenging system activity, was responsible for higher resistance of groundnut to A. flavus infection. Li et al . reported that enhancing resistance to brown rot caused by Monilinia fructicola in peach fruits by NO treatment may originate from the promotion of PAL , 4CL , C4H , CHS , and CHI gene expression and enzyme activity, resulting in higher phenol, flavonoid, and anthocyanin accumulation exhibiting antifungal capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also sulfur assimilation seems to be regulated by NO under stress conditions as mustard plants exposed to cadmium showed a NO‐triggered stimulated S‐assimilation and GSH production (Per, Masood, & Khan, ). Besides involvement in regulating primary metabolism, NO also regulates numerous secondary metabolite specific pathways including terpenoid production in Taxus chinensis (Wang & Wu ); anthocyanin and flavonoid biosynthesis activated by brassinosteroids (Li, Zhang, et al, ) or by cold acclimation (Costa‐Broseta et al, , ); and phenylpronaoid biosynthesis and triggered resistance to pathogens (Li, Zhu, et al, ; Santos‐Filho et al, ). In addition, NO also regulates the production of secondary metabolites of high nutraceutical value (Zhang, Zheng, & Wang, ).…”
Section: No As a Regulator Of Development And Stress‐related Responsesmentioning
confidence: 99%